Beyond the Textbook: Pedagogical Challenges and Curriculum Opportunities in Designing an ESP for Business Course at a Private Indonesian University - Abd. Syakur; Yulianto Sabat; Ika Rahmania; Lailatul Musyarofa; Moh. Hilman Fikri (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
Despite the expanding scholarship on English for Specific Purposes (ESP), insufficient attention has been given to the pedagogical and curricular consequences of developing ESP for Business courses in contexts where textbooks are unavailable, unsuitable, or intentionally excluded. Much of the existing literature remains anchored in textbook-dependent models, thereby overlooking how curriculum design, instructional practices, and learning coherence are negotiated in textbook-free settings. Addressing this gap, this study investigates the pedagogical challenges and curriculum opportunities emerging from the design of an ESP for Business course at Universitas Cipta Wacana, a private Indonesian university. Adopting a design-oriented qualitative research approach, the study examined iterative processes of course planning, materials development, and instructional enactment over one academic semester. The participants comprised 38 undergraduate Business Administration students and two ESP instructors, selected through purposive sampling. Data were generated from instructional design artifacts, teaching reflections, learner feedback instruments, and focused interviews with instructors, and were subjected to systematic qualitative analysis. The findings indicate that the absence of a prescribed textbook fostered curricular adaptability, contextual authenticity, and closer alignment with disciplinary communication practices, while simultaneously generating tensions related to instructional consistency, assessment benchmarking, and increased cognitive and temporal demands on instructors. These findings highlight the dual pedagogical implications of textbook-free ESP design and suggest the need for institutionally supported frameworks to sustain innovation while ensuring curricular coherence.